2020
DOI: 10.1001/jamainternmed.2020.0681
|View full text |Cite
|
Sign up to set email alerts
|

Seriously Ill Patients’ Willingness to Trade Survival Time to Avoid High Treatment Intensity at the End of Life

Abstract: Arbor), with survey formatting and deployment. He was not compensated for his work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 4 publications
5
31
0
Order By: Relevance
“…Patients preferred to pay the highest (RMB256,895.45) to obtain enhanced quality of life rather than life extension. These results present a more detailed and complicated picture of trade-offs between life extension and quality of life among terminal cancer patients, which complements and extends previous research [7,10,19]. Waller et al found Australian inpatients preferred end-of-life care reducing pain and discomfort as much as possible, even if it meant not living longer [7].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Patients preferred to pay the highest (RMB256,895.45) to obtain enhanced quality of life rather than life extension. These results present a more detailed and complicated picture of trade-offs between life extension and quality of life among terminal cancer patients, which complements and extends previous research [7,10,19]. Waller et al found Australian inpatients preferred end-of-life care reducing pain and discomfort as much as possible, even if it meant not living longer [7].…”
Section: Discussionsupporting
confidence: 81%
“…Rubin et al found that 86.7% of U.S. hospitalized seriously ill patients would trade at least one year of a five-year lifespan to avoid a scenario where they died in the ICU with moderate pain and suffering [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that patients’ perspectives differ from physicians’ in this respect as a recent study has shown that patients are willing to trade survival time to avoid end of life in an ICU. 17 Family opinion has been shown to significantly influence ICU admission decisions. 14 18 19 Family can either act as useful healthcare surrogates or make requests in response to their own needs.…”
Section: Discussionmentioning
confidence: 99%
“…11 The majority (87%) of seriously ill older adults who are hospitalized express that they would even trade 1 year of a 5-year lifespan to avoid dying in the ICU. 12 Unfortunately, the outcomes after ED intubation among seriously ill older adults are not as good as many patients think they will be, which may be predicted from prognosis calculators. 13,14 One in 3 older adults dies in the hospital after intubation.…”
Section: Familiarity With the Patient's Prognosis Is Essential Beforementioning
confidence: 99%